2016
DOI: 10.1177/1077699016674185
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Culture and Performance on Trust in News Media in Post-Communist Eastern Europe: The Case of Serbia

Abstract: This study tested the influences of cultural and performance factors on trust in news media in Serbia by conducting a survey on a stratified random sample of the population ( N = 544). The results show that both factors played a significant role, but that the performance explanation was slightly more powerful. The levels of trust in news media and generalized trust in Serbia remained low, while the perceptions of news media corruption reached extremely high levels. Before testing theories, the meanings of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Calls for the government to remove restrictions on the freedom of the press and to protect the independence of media were important public demands, both during the 1990s protests against the Milošević's regime and during the recent waves of anti-government protests started in 2018 (IREX, 2019;Rupar et al, 2019). A recent study has found that Serbian citizens perceive that newspersons, when making professional decisions, commonly engage in corruptive practices, i.e., yielding to the demands from the media owners or other external political and economic sources of power (Pjesivac et al, 2017). Such perceptions show that the public is unconvinced by the media's capacity to break free from the negative practices which, for long, have been governing the mass media in Serbia.…”
Section: The Media Environment and Public Perceptions Of The News Media In Serbiamentioning
confidence: 99%
See 2 more Smart Citations
“…Calls for the government to remove restrictions on the freedom of the press and to protect the independence of media were important public demands, both during the 1990s protests against the Milošević's regime and during the recent waves of anti-government protests started in 2018 (IREX, 2019;Rupar et al, 2019). A recent study has found that Serbian citizens perceive that newspersons, when making professional decisions, commonly engage in corruptive practices, i.e., yielding to the demands from the media owners or other external political and economic sources of power (Pjesivac et al, 2017). Such perceptions show that the public is unconvinced by the media's capacity to break free from the negative practices which, for long, have been governing the mass media in Serbia.…”
Section: The Media Environment and Public Perceptions Of The News Media In Serbiamentioning
confidence: 99%
“…Consequently, a great deal of research effort has been directed towards understanding the causes of such decline (for an overview, see McLeod, Wise & Perryman, 2017). In line with cultural and performance theories regarding institutional trust, previous studies have commonly analyzed media trust as a function of audience characteristics and/or media performance (Hanitzsch et al, 2018;Hopmann, Shehata & Strömbäck, 2015;Ladd, 2012;Pjesivac, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There should also be considerable variance between countries that have passed through different stages of transformation (see Mitropolitski 2016). The results of existing surveys point to a mixed picture: institutional performance explains most of the post-communist variables, such as low trust in political institutions (Hooghe and Quintelier 2014;Pjesivac 2017), but there are studies that show residuals that cannot be "explained away," such as confidence in political parties and civil society engagement (Bernhard and Karakoç 2007;Tucker 2011, 2013;Svenonius and Björklund 2018). Pop-Eleches and Tucker (2013) have accentuated the generational effect of totalitarianism.…”
Section: Tracing the Post-communist "Effect"mentioning
confidence: 99%
“…Ivanka Pjesivac (2017), who received her BA degree in Serbia, and has both her MS and PhD degrees from U.S. universities, analyzes the influences of cultural and performance factors on trust in news media in Serbia by a survey on a stratified random sample of the Serbian population. The paper focuses on a current topic of international interest, and the author is highly knowledgeable of the relevant literature of cultural and performance theories.…”
mentioning
confidence: 99%